Is beverage consumption associated with increased body weight among adolescents? - Karadavut, Bahar; Şahin, Habibe; Kaner, Gülşah; Karadavut, Serhat (Progress in Nutrition, 2017)
Background: Recently, considerable attention has been given to beverage intake as a source of calories which may be linked to pediatric obesity. Objective: To examine the association between beverage consumption and changes in weight status among adolescents. Material/Methods: A total of 600 adolescents, aged 14-18 years, were involved in the study. Body weight, height, and waist circumference were measured. BMI percentiles were calculated and adolescents were classified as normal weight, overweight, and obese. For the collection of data on beverage intake, the 24-h recall technique was used. Data on beverages were examined in milliliters. Results: Of the total 600 participants in our sample, 79.3% were considered to be of normal weight, 13.3% were overweight and 7.4% were obese. All of the adolescents consumed water. Tea was the second most commonly consumed beverage (80.8%), followed by sugar-sweetened beverages (SSBs, 49.3%), and whole fat milk (24.3%). Elevated consumption of water was associated with elevated weight, BMI and waist circumference. There was no evidence of an association among milk, fruit juice, SSBs, tea, coffee consumption and weight status. Conclusion: In this study, water intake was associated with obesity. Further studies investigating the relationship among beverage consumption, total energy intake, and development of obesity are needed.